2021
DOI: 10.1101/2021.05.20.445070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal evaporating droplet dynamics on fomites enhances long term bacterial pathogenesis

Abstract: Naturally drying bacterial droplets on inanimate surfaces representing fomites are the most consequential mode for transmitting infection through orofecal route. We provide a multiscale holistic approach to understand flow dynamics induced bacterial pattern formation on fomites leading to pathogenesis. The most virulent gut pathogen, Salmonella Typhimurium (STM), typically found in contaminated food and water, is used as model system in the current study. Evaporation-induced flow in sessile droplets facili… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…We also observed that the infectivity of the bacterium deposited at the edge is significantly higher than the center deposited bacteria. This could be primarily due to the upregulation of virulence genes upon enormous force exerted on the bacteria during the drying process [15]. We observe these similar observations for both SRF dried droplet and milliQ dried droplet, suggesting a possible role of physical force on the heightened virulence of the bacterium.…”
Section: Bacterial Survivability and Pathogenesis Aftermath Desiccati...supporting
confidence: 74%
See 1 more Smart Citation
“…We also observed that the infectivity of the bacterium deposited at the edge is significantly higher than the center deposited bacteria. This could be primarily due to the upregulation of virulence genes upon enormous force exerted on the bacteria during the drying process [15]. We observe these similar observations for both SRF dried droplet and milliQ dried droplet, suggesting a possible role of physical force on the heightened virulence of the bacterium.…”
Section: Bacterial Survivability and Pathogenesis Aftermath Desiccati...supporting
confidence: 74%
“…Bacteria inside droplets experience several physical stresses [15] such as shear stress due to fluid motion in the environment, starvation stress (caused due to lack of nutrients), desiccation stress (caused due to depletion of water from bacterial cell wall due to evaporation), and stress due to harsh environmental conditions (fluctuating humidity and temperatures), to name a few. The bacteria-laden droplets in contact with any surface will eventually evaporate and lead to a drastic loss in viability of the bacteria [16] due to desiccation at the end stage of evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, drying, exposure medium and their interaction had a more even contribution to variability of viable counts on silver compared to copper. The expected difference of silver having a larger effect in wet conditions and copper also excelling in dry conditions (15,30,31) was with some reservation confirmed for E. coli, but not for S. aureus at least partially, because silver had overall very low antibacterial activity towards S. aureus. Interestingly, while metal-based surfaces seemed more efficient towards E. coli, Si-Quat coating preferentially worked against S. aureus in low-organic medium and more importantly, its activity was not significantly affected by RH as none of the drying-related causes statistically significantly contributed to viable count variation.…”
Section: Effect Environmental Variables On Antibacterial Activitymentioning
confidence: 98%
“…Drying itself induces stresses due to desiccation, fluid motion and starvation as observed in previous works of our group. 65,66 As both stressed and unstressed sample were subjected to desiccation stresses, the effect of drying is common to both the samples and the differences in the morphology can be attributed explicitly to the flow stresses. To do so, we perform noncontact mode AFM to keep the type of stress applied to the Table 1 Summary of the stressing parameters used in the present study.…”
Section: Shear Stress Alters the Morphology Of Kpmentioning
confidence: 99%